COMPREHENSIVE METHODOLOGY FOR ASSESSING HUMAN CAPITAL AND PROBLEMS OF ITS ASSESSMENT - Черевач-Филипович, К.; Когут, О. (Journal of Economic Research & Business Administration, 2019)
The article discusses ways to assess human capital. In recent decades, the urgency of the problems associated with the assessment of human capital and its components has not only faded away, but also increased as the number of companies grew. The interest of economics in human creative abilities, in the ways of their formation and development has sharply increased. Issues of human capital valuation are of interest due to the complexity and versatility of this category, as well as its importance for the effective functioning of the economy. Given the intangible nature of human capital, manifested in the form of knowledge, skills, work and management skills, as well as its continuous accumulation and communication with specific employees, it should be noted that a specific set of criteria is less important than the process of measuring and using the information collected. The systems for evaluating human capital based on certain quantitative criteria are based on value and natural approaches to its definition. Methodological approaches to the economic definition of human capital, based on different models, develop ideas that provide new, more realistic options for evaluating human capital. The formation and development of human capital takes place with the direct participation of the family, the state, enterprises and various public funds. At present, when an employee of an organization must be constantly active in improving his abilities, it is necessary to take into account the fact that learning takes place throughout his life.